Eighteen new species of Oecetis McLachlan 1877 (Trichoptera, Leptoceridae) from New Caledonia - Johanson, Kjell Arne; Mary, Nathalie Jeanne; Sjöberg, Tin; Malm, Tobias (Zootaxa, 2020)
Eighteen new species of Oecetis are described, diagnosed, and illustrated from New Caledonia: Oecetis amphora sp. nov., Oecetis ovula sp. nov., Oecetis ramosa sp. nov., Oecetis loyolaensi sp. nov., Oecetis millei sp. nov., Oecetis christinae sp. nov., Oecetis rostrata sp. nov., Oecetis alicae sp. nov., Oecetis oxybelis sp. nov., Oecetis dorsospina sp. nov., Oecetis multidentata sp. nov., Oecetis gracilis sp. nov., Oecetis rostra sp. nov., Oecetis triramosa sp. nov., Oecetis flucta sp. nov., Oecetis nouvellecaledoniensis sp. nov., Oecetis variabilis sp. nov., and Oecetis ovata sp. nov. A diagnostic key is provided for males of Oecetis species of New Caledonia. The species display similarities in genitalic characteristics but also a high diversity of apomorphic features. The new species were collected from lotic habitats across most of Grande Terre.